(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Who is ready? How do schools reply to computer literacy challenges as a new normal because of the students in education delivery? This study’s main purpose was to determine the challenges in computer literacy on academic performance in complying with all the educational requirements and attending classes online. Nowadays, computer literacy is already a part of our life. Thanks to higher living demands like printed materials, tarps, social media accounts, applications, and news, every company that uses computers or new technology and even attends classes needs computer literacy not to be left behind. Everything is plagued by computer literacy. Computer Literacy is crucial in Bestlink College of the Philippines student’s academic performance. In new normal education, learners must be academically competent and computer literate to be ready to operate efficiently in academic contexts. Nowadays, BTVTED 3rd-year college students in Bestlink College of the Philippines are expected to be computer literate and able to operate effectively on computer or electronic. This shows that computer literacy should be included within the definition of educational literacy to allow it a more comprehensive meaning and a broader sense. Over the years, the fear of fogeys is computer literacy and regarded as a worldwide challenge within the education system and society Pk and Jetho, (2019); unless learners can quickly learn to adapt themselves in their personal and professional affairs and society at large, they’re destined for disappointment within the computer literacy space. Moreover, computer literate uses technology to perform their job more effectively and efficiently. In today’s new normal education, teaching is feasible but has challenges. Hence, many students were said to face challenges in computer literacy moreover because the challenges in coping because the classes are now online. This study will closely glance at online class practices that aim to see the challenges in computer literacy of the latest normal education that affect the student’s educational performance. The researchers used the descriptive method to determine the Impact of Computer Literacy on Student Academic Performance of BTVTED 3RD Year College Students at Bestlink College of the Philippines-Bulacan AY 2021-2022. The results showed that the impact of computer literacy is highly effective in the student’s academic performance and the complete things needed to use a computer efficiently and effectively. The students’ computer literacy effectively helps their academic performance, together with the help of the availability of devices, professors, and schools. Even if there are computer literacy challenges that can affect their students’ academic performance. The study’s findings are utilized to identify the impact of computer literacy on student academic performance. The main purpose is to improve learning through adapting and familiarizing computer literacy and lessen the problems students may encounter acquiring academic performance.